Growing Trend of China's Contribution to Global Diabetes Research: A Systematic Literature Review. Issue 18 (May 2016) - Zhao, Xiyan; Guo, Liangqing; Yuan, Mingze; He, Xinhui; Lin, Yiqun; Gu, Chengjuan; Li, Qingwei; Zhao, Linhua; Tong, Xiaolin
Abstract : Abstract: China, as a rapidly developing country with the largest population in the world, is playing an increasingly important role in diabetes research. There are >10, 000 diabetes doctors who care for a large population of diabetic patients. The quantity and quality of research on diabetes from 3 major regions of China, including Mainland China (ML), Taiwan (TW), and Hong Kong (HK), is unknown. We aimed to analyze the contributions of each of these 3 regions to diabetes research. Articles on diabetes originating from ML, TW, and HK that were published from 2005 to 2014 were retrieved from the Web of Science. The quantity of articles, citations, article types, and articles published in high-impact journals were analyzed. A total of 9302 articles were retrieved from the 3 regions of China. There were 6775 from ML, 1993 from TW, and 534 from HK, with an increasing trend in publications from 2005 to 2014. After 2006, the number of publications from ML exceeded TW and HK. The largest total number of citations (48, 296) was from ML. The highest mean citations, however, were from HK (15.90). PLoS One was the most popular journal in all 3 regions. The greatest number of RCTs, clinical trials, meta-analyses, and articles published in high-impact journals were from ML. There has been a significant increase in the number of articles published on diabetes research from China during the past 10 years. Most of the articles were published by authors in ML, and an increasing trend began in 2006. HK had the highest quality research output in terms of mean citations per article.